Genome sequencing and identification of candidate variants for a red/black color polymorphism in tilapia (Oreochromis spp.) - Behrens, Kristen A.; Danley, Aimee H.; Jailwala, Soumya; Kocher, Thomas D. (Aquaculture, 2025)
Red tilapia are favored by consumers, but the molecular genetic basis for this color pattern is unknown. Here we report on the genetic and physical mapping of the red locus in two strains of tilapia. We raised ∼3000 hybrid individuals to map the red locus to a single bacterial artificial chromosome clone on linkage group 3. Long-read sequencing allowed us to assemble contigs spanning both the black and red haplotypes. The red haplotype contains additional repetitive sequence totaling almost one megabase that includes no obvious candidate genes. We suggest that the red phenotype may arise from substitutions in a protein in the primary cilia (Ccdc149), or changes in the expression of a nearby gene (nckx2). Red mutations in several unlinked loci have now been identified, creating an opportunity to identify the best allelic combinations for aquacultural production. •Consumers prefer red-pigmented tilapia, but the genetic basis for this trait is unknown.•Genetic mapping narrowed the red locus to a small region of linkage group 3.•Long-read genome assembly identified an expansion of repetitive sequences totaling ∼1 Mb in the red allele.•Variation in either ccdc149a or nckx2 might be responsible for the red phenotype.•Combinations of several unlinked loci may produce the best red tilapia for aquaculture.